The Delaware General Corporation Law: Business Corporations Merger (consolidation) Transactions - Stanislav E. Kuzmin (Московский журнал международного права, 2015)
The study and analysis of U.S. law on mergers and acquisitions of companies (corporations) from the standpoint of comparative legal studies allow more accurately and deeper to represent the state of the modern foreign legislation in the sphere of corporate regulation, to identify the features of such regulation, to provide an analysis of its development prospects and opportunities of influence on the Russian economic agents. Since the most popular jurisdiction for registration of corporations in the United States is Delaware, in this article will be considered issues of legal regulation of conduct of merger (consolidation) on the example of the General Corporation law of this state. The pattern of regulation of merger (consolidation) of the state of Delaware is followed by the majority of the United States.